Cocaine sale restriction (leaflet) (1916)
1916 1916 1910s 2 pages COCAINE RESTRICTION. WHAT IT MEANS TO THE WAGE EARNER. THE HOME OFFICE has invoked an ORDER IN COUNCIL to prohibit the buying, selling, possession or use of COCAINE except to registered medical practitioners, dentists, chemists, and other persons possessing a special permit, in order (rightly) to prohibit its misuse by soldiers and those engaged in war organizations. Special permits have been refused to unregistered dental practitioners. THE INCORPORATED DENTAL SOCIETY (the Society representing the unregistered practitioners) desires to draw the attention of TRADES-UNION REPRESENTATIVES to the following facts:— 1.— Almost the whole of the dental practice amongst WAGE EARNERS is done by UNREGISTERED PRACTITIONERS because of the exclusiveness and high charges made by the REGISTERED practitioners. 2.— There are ONLY 5,400 REGISTERED dental practitioners in the United Kingdom (of whom 1,400 have no recognised training or passed any examination). Whole districts exist without ANY registered practitioner. EXAMPLE:— The Forest of Dean parliamentary constituency, 147,000 acres in extent, with a population of 56,000 persons, chiefly occupied as miners, has not a single registered dentist resident in the division. 3.— The unregistered dental practitioner has used COCAINE Analgesia with marked success for the PAINLESS EXTRACTION OF TEETH during the past 30 years. About 100,000 teeth are so extracted daily. 4.— The Home Office suggests substituting supplies of NOVOCAIN, a German patented product. The standard product is combined with Adrenine, which is a vaso-constrictor, and is not a desirable drug for dental use. Cocaine does not require Adrenine. Whenever deaths after analgesics have taken place (these are very few in proportion to many millions of operations, and have occurred alike amongst registered and unregistered practitioners) it has been due chiefly to diseased kidneys and the Adrenine drug. 5.— There is no question of public danger involved in the use of Cocaine, or the Home Secretary would not have extended the permit from July 28th to October 15th. The true object appears to be a MONOPOLY for the Registered. 6. — If the Home Office Order must stand and permits are still refused the WAGE EARNERS will be largely prohibited from RECEIVING PAINLESS DENTAL TREATMENT. 7.— Protection against the misuse of COCAINE can easily be taken at the SOURCE OF SUPPLY. If necessary permits can be issued to unregistered dental practitioners by CLERKS TO LOCAL AUTHORITIES, who would be in a position to know the bona fide practitioner. This would save the trouble of licenses being reviewed by the Home Office; the enormous work involved to his department was the burden of a complaint made by the Home Secretary. The WAGE EARNER will be the first to suffer if the Order is persisted in as regards the unregistered dental practitioner. As a TRADES UNION REPRESENTATIVE you should SIGN THE PETITION to the Home Secretary, which is in charge of Councillor W.L. Edwards, of Gloucester, at the ENTRANCE TO THE CONGRESS. 292C/11.1/1/2/10